Single-cell RNA sequencing reveals anterograde trans-synaptic degeneration and exacerbated synaptic remodeling in myopia - Ruixue Zhang; Yunxiao Xie; Miao Zhang; Zhiheng Li; Lijie Guo; Huixia Wei; Xiaomeng Li; Jizhao Xin; Zhaohui Yang; Ying Wen; Jiawen Hao; Xianglin Li; et al. (Experimental and Molecular Medicine)
Abstract Myopia is a serious public health issue worldwide. Damage to retinal ganglion cells (RGCs) in the retina induces degeneration of the visual cortex, which is known as anterograde trans-synaptic degeneration (TSD). However, the role of TSD in myopia is still unknown. Here single-cell RNA-sequencing revealed the activation of RGC apoptotic signals in the retinal ganglion and the remodeling of synapses in the visual cortex in myopia. The thickness of the retinal nerve fiber layer was negatively correlated with the degree of damage to the visual cortex and damage to neurons in the visual pathway and to the synaptic structure and function of the visual cortex indicated the occurrence of anterograde TSD in the visual pathway. The knockdown of Fos, which inhibited retinal neuronal apoptosis, suppressed TSD, indicating that myopia can aggravate RGC apoptosis, induce anterograde TSD and thus aggravate synaptic remodeling. Our findings provide a new experimental basis for understanding the pathogenesis of myopia.